Pelaksanaan Penyelidikan Terhadap Tersangka Tindak Pidana Persetubuhan Anak Dibawah Umur Di Kepolisian Sektor Kempas (Studi Kasus Nomor : LP/B/06/VII/2025/SPKT/SEK.KEMPAS) - Muhammad Murdani; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to examine the implementation of investigations into suspects of sexual intercourse crimes involving minors at the Kempas Sector Police based on Case Number LP/B/06/VII/2025/SPKT/SEK.KEMPAS and to identify the obstacles and efforts encountered during the investigation process. This research employed an empirical legal research method using a descriptive analytical approach. Data were collected through interviews, observations, and literature studies and analyzed qualitatively using a deductive method. The results indicate that the investigation process begins with receiving police reports, collecting preliminary information, examining the crime scene, interviewing witnesses, and gathering sufficient preliminary evidence before proceeding to the investigation stage in accordance with criminal procedural law. The investigation process faces several obstacles, including limited evidence, difficulties in obtaining statements from victims and witnesses, the psychological condition of child victims, and limited investigative personnel. To address these obstacles, the Kempas Sector Police coordinate with the Women and Children Protection Unit, psychologists, village authorities, and optimize investigative techniques in accordance with applicable legal provisions.